The Effect of Very-low-dose Warfarin on Markers of Hypercoagulation in Metastatic Breast Cancer: Results from a Randomized Trial - Falanga, A.; Levine, M. N.; Consonni, R.; Gritti, G.; Delaini, F.; Oldani, E.; Julian, J. A.; Barbui, T. (Thrombosis and Haemostasis, 1998)
Malignancy is a risk factor for thromboembolism and anti-cancer chemotherapy can increase this risk. Prophylaxis of thrombosis with very-low-dose warfarin given concurrently with chemotherapy has a significantly reduced rate of thromboembolism in a randomized trial in women with stage IV breast cancer. In a group of 32 patients randomized in one center (16 subjects on warfarin and 16 on placebo), we have prospectively studied the plasma levels of: 1. Markers of ‘in vivo’ clotting activation (thrombin-antithrombin complex [TAT], prothrombin fragment 1+2 [F1+2] and D-dimer), 2. Factor VII (FVII), and 3. Natural anticoagulants (protein C [PC] and antithrombin [AT]). The aims of this study were: 1. to examine whether laboratory tests predicted those patients who developed thrombosis, and 2. to evaluate the effect of very-low-dose warfarin on hemostatic variables. The patients’ hemostatic parameters were evaluated before entry into the study and after starting chemotherapy ± prophylaxis, before each course for nine courses. Before-treatment results were compared to those of a sex and age-matched non-cancer control group. There was a significant elevation of plasma levels of TAT (p <0.001), F1+2 (p <0.001), D-dimer (p <0.0001) and FVIIa (p <0.05), as well as an increase of FVII proteolysis (p <0.05), whereas plasma PC and AT concentrations were not different from controls. After starting chemotherapy, markers of clotting activation were progressively lower in the group receiving warfarin prophylaxis compared to the group on placebo. Differences between the groups became statistically significant (p <0.01) after the 4th course of chemotherapy. Deep vein thrombosis occurred in two patients in the placebo arm. The results of this study indicate that before therapy, an hypercoagulable state is present in stage IV breast cancer, and after starting chemotherapy, abnormalities of hypercoagulation markers persist, however they are reduced by very-low-dose-warfarin. None of the laboratory variables could predict thrombosis in the single patient.